2014
DOI: 10.1021/la500766t
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Functionalized Nanostructured Biointerfaces by Click Chemistry

Abstract: The presentation of biologically active molecules at interfaces has made it possible to investigate the responses of cells to individual molecules in their matrix at a given density and spacing. However, more sophisticated methods are needed to create model surfaces that present more than one molecule in a controlled manner in order to mimic at least partially the complexity given in natural environments. Herein, we present dual-functionalized surfaces combining quasi-hexagonally arranged gold nanoparticles wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 34 publications
0
56
0
Order By: Relevance
“…The molar ratio of c(RGDfK)-azobenzene and PEG2000 was adjusted to 1:99, which has recently been reported to offer adequate adhesion conditions for fi broblast cells. [ 21 ] It corresponds to a c(RGDfK)-azobenzene packing density of ≈0.5 molecules/nm 2 , as determined with UV-vis spectroscopy. Figure 1 B illustrates the working hypothesis of the mixed c(RGDfK)-azobenzene/PEG2000 monolayer.…”
Section: Doi: 101002/adma201504394mentioning
confidence: 96%
“…The molar ratio of c(RGDfK)-azobenzene and PEG2000 was adjusted to 1:99, which has recently been reported to offer adequate adhesion conditions for fi broblast cells. [ 21 ] It corresponds to a c(RGDfK)-azobenzene packing density of ≈0.5 molecules/nm 2 , as determined with UV-vis spectroscopy. Figure 1 B illustrates the working hypothesis of the mixed c(RGDfK)-azobenzene/PEG2000 monolayer.…”
Section: Doi: 101002/adma201504394mentioning
confidence: 96%
“…The PHSRN sequence is needed to achieve full adhesive activity for the α 5 β 1 integrin receptor. Previous research has shown that high affinity binding requires this synergy site to be engaged [57,58], and that availability of both the synergy site and RGD has significant impact on cell adhesion [38,59]. Hence, CAS is clearly superior to RGD in initial cell adhesion.…”
Section: Cell Detachment Forces Are Controlled By Surface Biofunctionmentioning
confidence: 99%
“…Although the binding affinity of RGD has strongly been improved by cyclization of the RGD sequence [34,35], which is realized by adding flanking residues and constraining the conformation of the RGD motif to a loop [36,37], the RGD binding sequence does not recapitulate the full functionality of ECM proteins. Native proteins contain multiple cell-binding sequences, which allow dynamic and simultaneous binding to cellular receptors and positively trigger cell adhesive events [38].…”
Section: Introductionmentioning
confidence: 99%
“…They immobilized the integrin binding motifs PHSRN and RGD in one molecule on titanium and could show beneficial influence on osteoblast-like cell behavior over a mixture of both peptides. Defined spatial distributions could be also realized by a patterned surface displaying PHSRN and RGD, which also resulted in a positively synergic effect on cell fate (Schenk et al, 2014).…”
Section: Combining Multifunctionality On a Biomaterials Surfacementioning
confidence: 99%
“…While employing a bioinert background by PEG chains, cell-attracting cRGD was immobilized on gold nanoparticles and PHSRN was coupled by CuAAC to the silanized glass surface. The defined distribution of these peptides had a pronounced impact on cell number, area and the generation of focal contacts (Schenk et al, 2014). In Figure 5E it is schematically shown how the requirements of cardiovascular biomaterials can be implemented in an experimental setup.…”
Section: Trigger Cell Function In a Bioinert Backgroundmentioning
confidence: 99%